Efektifitas Ekstrak Serai (Cymbopogon nardus L) Dan Daun Belimbing Wuluh (Averrhoa blimbi) Terhadap Kesintasan Telur Keong Mas (Pomacea canaliculata L) (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2023)
The golden snail is a pest that interferes with agricultural yields. Golden snail pests can be controlled with pesticides in the form of molluscicides. The use of pesticides causes damage to the environment and the health of farmers. By reducing the residual effects resulting from the use of pesticides, alternatives are needed to control the golden snail pest, such as the use of natural materials, namely lemongrass and starfruit leaves. The lemongrass plant (Cymbopogon nardus L) is a plant that has bioactive compounds such as citronella while the cucumber tree (Averrhoa blimbi) contains flavonoids, tannins and saponins as active compounds. The golden snail used is a large and old golden snail with a yellow-black shell characteristic. The purpose of this study was to determine the effectiveness of mixing lemongrass and cucumber tree leaves extracts on the survival rate of golden snail eggs. The research was conducted by soaking golden snail eggs using a mixture of lemongrass extract and cucumber tree leaves at concentrations (%w/v) of 0%, 15%, 25% and 50%. The results showed that the most effective mixing of lemongrass and cucumber tree leaves extracts in increasing the survival rate of golden snail eggs was a concentration of 50% with a survival rate value of 100% at the most optimum conditions for 14 days Keywords : survival rate, golden snail eggs, lemongrass, wuluh cucumber tree leaves